알레르기성 접촉성 피부염에 대한 加味芎歸湯의 억제효과 - 안지영(Ji Young Ahn); 임이랑(Lee Rang Im); 김준호(Jun Ho Kim); 신명걸(Mingjie Xin); 권세욱(Se Uk Kwon); 김대근(Dae Keun Kim); 송봉석(Bong Suk Song); 송봉준(Bong Jun Song); 정현주(Hyun Ju Jung); 홍승헌(Seung-Heon Hong); 권동렬(Dong-Yeul Kwon); 김윤경(Yun Kyung Kim); et al. (동의생리병리학회지, 2010)
Gamigunggui-tang (GMGGT) is one of the important prescriptions that has been used in oriental medicine. We investigated the inhibitory effect of an oral administration of hot water extract of GMGGT on the development of atopic dermatitis (AD) by using Balb/c mice. The induction of atopic dermatitis-like lesion was conducted by the removal of the back hairs and topical application of 2,4-Dinitrochlorobenzene (DNCB) on to the back skin repeatedly. GMGGT was orally administered at a different dose (10.0 mg/kg, 50.0 mg/kg). Skin reactions, consisting of increased ear thickness and the presence of ear inflammation, were observed in mice over three weeks. Oral administration of GMGGT significantly suppressed the skin lesions, ear swelling, spleen weight, total serum IgE in a concentration dependent manner, and also inhibited the infiltration of mast cells in the dorsal skin. In the present study, these results suggested that GMGGT extract inhibits inflammatory response atopic dermatitis. Therefore, GMGGT may be effective substances for the management of AD in human. KCI Citation Count: 6